Corrigendum to “Metal-based curcumin and quercetin complexes: cell viability, ROS production and antioxidant activity” [Journal of Molecular Structure 1245 (2021) 131107] (Journal of Molecular Structure (2021) 1245, (S0022286021012382), (10.1016/j.molstruc.2021.131107)) - Altundağ, Ergül Mutlu; Özbilenler, Cahit; Ustürk, Selma; Kerküklü, Namık Refik; Afshani, Masoud; Yilmaz, E. (Elsevier B.V., 2025)
In the original version of this article, a duplication error was identified in Figure 8, which presented the coordination complexes of curcumin and quercetin with magnesium and calcium ions. Duplicated image can be seen in the bottom middle part of the figure, which corresponds to coordination complex of quercetin with magnesium. Due to duplication error, image of coordination complex of quercetin with calcium was inserted instead of magnesium. The corrected version of Figure 8 is provided below and accurately reflects the intended molecular compositions.[Figure presented] This correction does not affect the results or conclusions of the study. The authors apologize for any inconvenience caused. © 2025 Elsevier B.V.